2016
DOI: 10.1124/jpet.116.233304
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sensitivity of  3 4 Nicotinic Receptors in Enteric Neurons after Long-Term Morphine: Implication for Opioid-Induced Constipation

Abstract: Opioid-induced constipation is a major side effect that persists with long-term opioid use. Previous studies demonstrated that nicotine-induced contractions are enhanced after long-term morphine exposure in guinea pig ileum. In the present study, we examined whether the increased sensitivity to nicotine could be observed in single enteric neurons after long-term morphine exposure, determined the subunits in mouse enteric neurons, and examined the effect of nicotine in reversing opioid-induced constipation. Nic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…An α3β4 nicotinic receptor agonist increased fecal pellet output in mice treated chronically but not acutely with morphine. These data suggest that tolerance to the inhibitory effects of morphine on gut motility may be due in part to upregulation of α3β4 nicotinic receptors on small intestinal myenteric neurons (Gade et al , 2016). …”
Section: Actions Of Opioid Drugs On Myenteric Neurons and Gut Motilitymentioning
confidence: 97%
See 1 more Smart Citation
“…An α3β4 nicotinic receptor agonist increased fecal pellet output in mice treated chronically but not acutely with morphine. These data suggest that tolerance to the inhibitory effects of morphine on gut motility may be due in part to upregulation of α3β4 nicotinic receptors on small intestinal myenteric neurons (Gade et al , 2016). …”
Section: Actions Of Opioid Drugs On Myenteric Neurons and Gut Motilitymentioning
confidence: 97%
“…This effect would suppress interneuronal and neuromuscular transmission (Smith et al , 2012). Myenteric neurons in the guinea pig and mouse small intestine express nicotinic receptors composed of α3 and β4 subunits and these receptors mediate most fast excitatory postsynaptic potentials in the myenteric plexus (Zhou et al, 2002; Gade et al, 2016). Studies of mouse small intestinal myenteric neurons maintained in primary culture showed that nicotine-induced inward currents were larger in neurons exposed to morphine for 16–24 hours compared to neurons exposed to morphine for 1 hour.…”
Section: Actions Of Opioid Drugs On Myenteric Neurons and Gut Motilitymentioning
confidence: 99%
“…There is increasing evidence that enteric neurons and gut‐innervating extrinsic neurons can modulate the response of the intestinal epithelial barrier to gut microbiota 46–48 . Morphine is known to modulate the excitability of these neurons by altering the activity of voltage‐gated ion channels 12,49–52 . Thus, altered activity of neurons might form the basis for opioid‐induced intestinal barrier dysfunction and the resultant dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…VIPergic neurons have been shown to regulate the activity of intestinal epithelial cells via crosstalk with innate lymphoid cells, ILC2, and ILC3 [36][37][38] . Morphine is known to modulate the excitability of enteric neurons by altering the activity of voltage-gated ion channels [39][40][41][42] . Morphine can also alter the expression of IL-18 in enteric neurons via opioid receptors 25 .…”
Section: Discussionmentioning
confidence: 99%